Internationalization of grocery retailers in emerging markets – general considerations and economic impacts - Elmar Kulke; Lech Suwala (Geographisches Institut, Humboldt-Universität zu Berlin, 2015)
General retailing was, and is still often considered to be a prevailing domestic economic activity. Trends, however, are changing. In the meantime, an internationalization of retailing, which took off at least 40 years ago allowed for the development of a coexistence of both domestic and international structures. Despite the unimpeded success of globalization's benefits in many industries, the `big picture' in grocery retailing is – with a few exceptions – somehow different. On the contrary to other industries or general retailing, grocery retailing is still dominated by local companies in most countries. Even in the wake of general trends like a worldwide liberalization of retail trade, a growing middle class or a higher penetration with personal vehicles or refrigerators in many developing countries, international players often could not get a hold on or are actually absent from the key retail markets. Every grocery retailer that had tried to expand to overseas markets failed as often as it has succeeded. This paper analyses global business opportunities derived from the process of internationalization of grocery retailing with special regard to developing economies and emerging markets in South America, Africa/ Middle East and Asia. Whilst the first part explores (1a) general trends of internationalization, (1b) conditions for market penetration and (1c) spatial patterns of expansion, the second part highlights (2a) economic impacts by means of a stylized model on the (2b) structure and (2c) dynamics of the market system.
Keywords: L81; F23; O19; R30; F61; 330; Internationalisation of Grocery Retailers; Retail Industry; Emerging Markets; Global South; Spatial Patterns of Corporate Expansion; Economic impacts of grocery internationalization